Experimental study on the submerged steam jet through side hole nozzle. Issue 1 (September 2015) - Wang, W; Yuan, F; Zhao, Q B; Chong, D T; Chen, W X; Yan, J J
Abstract: In this paper, the steam shape parameters and the condensation oscillation characteristics of the direct contact condensation of submerged steam jet into subcooled water were investigated through a side hole nozzle. Meanwhile, the dimensionless jet length and the expansion ratio versus pool water temperature and steam mass flux were obtained by measuring the photographs taken by a high speed camera. Both of them increased gradually with rise of pool water temperature and steam mass flux. A comparison of the shape parameters of three different style nozzles was also achieved. And a correlation of the dimensionless jet length was obtained, the predicted data agreed well with the experimental data, while the discrepancy was within ±5%. For the pressure oscillation versus steam mass flux, the peaks and the root mean square value of pressure oscillation were almost consistent in the range of 150-400 kg·m -2 ·s -1, while both of them increase in the range of 400-800 kg·m -2 ·s -1 . The positive peak and negative peak were completely symmetrical.